2021
DOI: 10.1177/1098214020931941
|View full text |Cite
|
Sign up to set email alerts
|

When Seeing Is Believing: Generalizability and Decision Studies for Observational Data in Evaluation and Research on Teaching

Abstract: Observations are widely used in research and evaluation to characterize teaching and learning activities. Because conducting observations is typically resource intensive, it is important that inferences from observation data are made confidently. While attention focuses on interrater reliability, the reliability of a single-class measure over the course of a semester receives less attention. We examined the use and limitations of observation for evaluating teaching practices, and how many observations are need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Mobbs et al aimed at the challenges of big data in enhancing the availability of university students' IPE and discussed the countermeasures of big data for enhancing the availability of university students' IPE [ 15 ]. Weston et al studied how to use Web mining technology and combine existing clustering technology to achieve high accuracy classification and clustering of Web text data [ 16 ]. Nurse et al built an instructional resource recommendation system based on online education, and designed and implemented each module of the system; describe the development platform and tools, and test the actual development effect [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…Mobbs et al aimed at the challenges of big data in enhancing the availability of university students' IPE and discussed the countermeasures of big data for enhancing the availability of university students' IPE [ 15 ]. Weston et al studied how to use Web mining technology and combine existing clustering technology to achieve high accuracy classification and clustering of Web text data [ 16 ]. Nurse et al built an instructional resource recommendation system based on online education, and designed and implemented each module of the system; describe the development platform and tools, and test the actual development effect [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…, 2018 ), but two different research groups have since demonstrated that four observations are often inadequate to reliably document instructional change across time ( Sbeglia et al. , 2021 ; Weston et al. , 2021 ).…”
Section: Future Directions For Research On Co-teaching For Pedagogica...mentioning
confidence: 99%
“…There is ongoing debate about the extent to which observer ratings can be used to judge teachers’ instructional quality. Some researchers argue that observer ratings should be used as one piece of evidence in a broader evaluation process (e.g., Lei et al, 2018; Van der Lans, 2018), while others question the validity and fairness of using such observer ratings (e.g., Praetorius et al, 2014; Weston et al, 2021). On the one hand, some prior studies have found that observer ratings of instructional quality are consistent across different observers and occasions, and that they correlate with other measures of instructional quality, such as student ratings and student learning outcomes (Hill et al, 2012; Van der Lans, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%